Deregulated Phosphorylation of CENH3 at Ser65 Affects the Development of Floral Meristems in Arabidopsis thaliana - Demidov, Dmitri; Heckmann, Stefan; Weiss, Oda; Rutten, Twan; Dvořák Tomaštíková, Eva; Kuhlmann, Markus; Scholl, Patrick; Municio, Celia Maria; Lermontova, Inna; Houben, Andreas (Frontiers in Plant Science, 2019)
Several histone variants are posttranslationally phosphorylated. Little is known about phosphorylation of the centromere-specific histone 3 (CENH3) variant in plants. We show that CENH3 of Arabidopsis thaliana is phosphorylated in vitro by Aurora3, predominantly at serine 65. Interaction of Aurora3 and CENH3 was found by immunoprecipitation in A. thaliana and by bimolecular fluorescence complementation. Western blotting with an anti-CENH3 pS65 antibody showed that CENH3 pS65 is more abundant in flower buds than elsewhere in the plant. Substitution of serine 65 by either alanine or aspartic acid resulted in a range of phenotypic abnormalities, especially in reproductive tissues. We conclude that Aurora3 phosphorylates CENH3 at S65 and that this post-translational modification is required for the proper development of the floral meristem.